"Just-in-Time" Personal Preparedness: Downloads and Usage Patterns of the American Red Cross Hurricane Application During Hurricane Sandy. (28th June 2016) - Kirsch, Thomas D.; Circh, Ryan; Bissell, Richard A.; Goldfeder, Matthew
Abstract: Objective: Personal preparedness is a core activity but has been found to be frequently inadequate. Smart phone applications have many uses for the public, including preparedness. In 2012 the American Red Cross began releasing "disaster" apps for family preparedness and recovery. The Hurricane App was widely used during Hurricane Sandy in 2012. Methods: Patterns of download of the application were analyzed by using a download tracking tool by the American Red Cross and Google Analytics. Specific variables included date, time, and location of individual downloads; number of page visits and views; and average time spent on pages. Results: As Hurricane Sandy approached in late October, daily downloads peaked at 152, 258 on the day of landfall and by mid-November reached 697, 585. Total page views began increasing on October 25 with over 4, 000, 000 page views during landfall compared to 3.7 million the first 3 weeks of October with a 43, 980% increase in views of the "Right Before" page and a 76, 275% increase in views of the "During" page. Conclusions: The Hurricane App offered a new type of "just-in-time" training that reached tens of thousands of families in areas affected by Hurricane Sandy. The app allowed these families to access real-time information before and after the storm to help them prepare and recover. ( Disaster Med Public Health Preparedness . 2016;page 1 of 6)